Grammatical cohesive devices in Tiếng Anh 12 reading texts and their Vietnamese equivalents / Le Thi Xuan; Supervisor: Assoc.Prof.Dr. Ho Ngoc Trung - Le, Thi Xuan
The thesis deals with the use of grammatical cohesive devices in the reading texts in the textbook “Tiếng Anh 12” and the Vietnamese equivalents in “Học tốt Tiếng Anh 12”. In the thesis, the theoretical background knowledge is based on the viewpoints of Halliday and Hasan (1976). The data was collected from the ten reading passages extracted from the new English textbook for grade 12 students, called “Tiếng Anh 12”, first published in 2015 and the Vietnamese equivalents in “Học Tốt Tiếng Anh 12”. Combinations of methods such as descriptive, statistic and contrastive analysis are used with a view to: Firstly, investigating the frequency and distribution of grammatical cohesive devices used in the chosen English texts; Secondly, finding out the similarities and differences between English texts and their Vietnamese translation in terms of the cohesive devices used and their semantic relationships, as well as the possible occurrences of cohesion shifts. Findings reveal that Vietnamese and English have more similarities than differences in terms of grammatical cohesive devices, but there are significant differences in the frequency of their occurrence. The similarities are significantly preserved for the purpose of accurateness, transparency and formality. Accordingly, not all English grammatical cohesive devices are translated into Vietnamese which causes a lot of challenges in learning and teaching this phenomenon. Related recommendations are suggested in the hope of providing English teachers and their students with some useful strategies in teaching and learning grammatical cohesive devices in general, and in teaching and learning reading and writing skills in particular more effectively.